Baja SAE USB as if project-oriented learning from the perspective of the paradigm of complexity - Renzo Boccardo Irigoyen (Universitat Politècnica de València, 2015)
Since technological development generates profound changes in our society and culture, it is important to be  prepared  for  these  modifications. Nowadays,  information  is  available  in any computer connected to the internet. Moreover, wisdom is associated with significant  knowledge  and,  therefore, every individual must build their knowledge  linking  it  to  previous experiences. In this context, it is essential to  introduce  changes  in  educational systems to prepare professionals able to deal within this changing dynamical situations. In this article are presented some theories related with the need of a new epistemological paradigm in order to understand teaching concepts, moreover the complex paradigm is proposed that provides  the  systematic  vision  of  the problem,  highlighting  the  importance of  the  existing  relationship  between the elements to be studied. A brief review of the conceptual methodology of the project-based learning as a learning  alternative.  Additionally,  the epistemological approach to complexity and its primary principles are discussed. Finally, a practical case of study in the Simon Bolivar University (Caracas, Venezuela) is described, in which a project-based learning from the point of view of complexity paradigm is demonstrated. Students are gathered as a team and based in the project-based learning; they design, build and try an all terrain prototype following the rules of the Automotive Society of Engineering of the United States to compete internationally.